The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1126/science.1131693
|View full text |Cite
|
Sign up to set email alerts
|

Activity- and mTOR-Dependent Suppression of Kv1.1 Channel mRNA Translation in Dendrites

Abstract: Mammalian target of rapamycin (mTOR) is implicated in synaptic plasticity and local translation in dendrites. We found that the mTOR inhibitor, rapamycin, increased the Kv1.1 voltage-gated potassium channel protein in hippocampal neurons and promoted Kv1.1 surface expression on dendrites without altering its axonal expression. Moreover, endogenous Kv1.1 mRNA was detected in dendrites. Using Kv1.1 fused to the photoconvertible fluorescence protein Kaede as a reporter for local synthesis, we observed Kv1.1 synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
274
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(282 citation statements)
references
References 28 publications
7
274
1
Order By: Relevance
“…Our results are consistent with other recent findings showing that activity deprivation produces a decrease in the expression of Kv1.1 channels in hippocampal (Grosse et al, 2000;Raab-Graham et al, 2006) and auditory brainstem neurons (Lu et al, 2004). Studies examining homeostatic plasticity have primarily focused on measurements in individual neurons, yet given the fact that homeostasis can be a global event affecting all members in a network begs the question as to the network effect of homeostasis.…”
Section: Homeostatic Plasticity and Network Synchronysupporting
confidence: 82%
“…Our results are consistent with other recent findings showing that activity deprivation produces a decrease in the expression of Kv1.1 channels in hippocampal (Grosse et al, 2000;Raab-Graham et al, 2006) and auditory brainstem neurons (Lu et al, 2004). Studies examining homeostatic plasticity have primarily focused on measurements in individual neurons, yet given the fact that homeostasis can be a global event affecting all members in a network begs the question as to the network effect of homeostasis.…”
Section: Homeostatic Plasticity and Network Synchronysupporting
confidence: 82%
“…45,46 Conversely, the translation of specific mRNAs can be actively inhibited by mTORC1 activity; one example is the translation of the voltage-gated potassium channel KV1.1. 47 Thus, while we can conclude that the global rates of ribosome activity are similar in chronically rapamycintreated and S6K1 −/− mice compared with controls, we cannot rule out subtle changes in translational activity on the level of specific mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…shown to be predominantly localized to axons, Jan and colleagues designed a reporter with Kaede fused to the amino terminus of the potassium channel protein Kv1.1 and whose mRNA also contained the 3 0 UTR of Kv1.1 (Raab-Graham et al 2006). On photoconversion and rapamycin treatment, the investigators observed new Kaede-Kv1.1 expression in distal regions of the dendrites indicating that the 3 0 UTR contributes to the dendritic localization of the mRNA and subsequent stimulation-dependent translation of Kv1.1 (Fig.…”
Section: Single-cell Imagingmentioning
confidence: 99%